(untitled) (Research, Society and Development, 2021)
Objective: To analyze the geospatial distribution of hepatitis B virus (HBV) in the State of Pará, Brazil, from 2010 to 2020 relating to hepatites B vaccination. Methodology: In this descriptive and cross-sectional work, data from the Information System of Notifiable Diseases, the Ministry of Health (MH) and the Brazilian Institute of Geography and Statistics were used. Results: The number of hospitalizations for HBV was decreasing from 2014 to 2018 and increased again in 2019 and 2020. Metropolitan Region I – Ananindeua, Belém, Benevides, Marituba e Santa Barbara do Pará – concentrated most of the notifications with high incidence of the cases in Belém and Ananindeua. Inside, the city of Redenção and Santarém also registered large number of notifications. Alenquer, Paragominas and Barcarena stand out for the higher mortality rate. Concomitantly, Pará is one of the states with the lowest vaccination coverage against Hepatitis B, being below the target of vaccine coverage since 2012. It is noteworthy in this scenario, that a little more than 20% of the 144 municipalities in the state are within the target established by the MH, especially the Marajó Health Region with the lowest vaccination coverage rate in the state. Conclusion: The low vaccination coverage and the results of the health indicators of hepatitis B showed a serious problem regarding public health in the state of Pará. Since the maintenance of immunization levels below the recommended in Pará presents a potential risk of interfering with the increase in cases, hospitalizations and deaths resulting from HBV.